Dynamics of the availability of available moisture in soil by optimization of sowing time and density of statement of sunflower plants in the Right-Bank Steppe of Ukraine - Pinkovskyi, Hennadii; Tanchyk, Semen (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Abstract. The article presents the results of scientific researches on the influence of sowing time and density of standing of sunflower plants on the dynamics of the content of available moisture in soil in the conditions of the Right-bank Steppe of Ukraine. One of the decisive factors for the achievement of high and sustainable crop yields in the conditions of unstable moistening of the Right-Bank Steppe of Ukraine is the accumulation and rational use of moisture, which is one of the most important unregulated factors limiting the yield. On average, during the years of research, the most available moisture in the 0-10 cm soil layer was in the first sowing period - when it was heated to a depth of seed 5 - 60C and was 25.0 mm. It was found that the moisture available to plants in the meter layer of soil at the time of sowing remained high and significantly influenced the dynamics of emergence of seedlings. On average, during the years of research, the most available moisture in the 0-100 cm soil layer was during the first sowing period - for warming it to a depth of seed 5 - 60C - 178.6 mm. In such conditions, quite favorable conditions of moistening of the sowing layer of soil are created in order to receive friendly and complete seedlings when sowing in the first - second decade of April. However, at the end of the third decade of April, there is a significant decrease in gross moisture reserves in the sowing and deeper layers of soil, which limits the productivity of crops. Of particular importance for sunflower plants is the content of available moisture in the 0 - 100 cm layer of soil after the formation of baskets. During this period, the sunflower intensively consumes the available moisture from the deeper layers of soil. Analyzing the results of the research, it should be noted that in most cases, a higher seed yield in sunflower hybrids was formed in those variants where the period from the formation of the basket to flowering occurred in June or the first decade of July, regardless of the year of fall medium long-term indicators. It was also found that the moisture available to plants in the meter layer of soil in the flowering phase was different during the years of research and varied in terms of sowing and depended on the density of plants. The highest moisture reserves available to the plants in the soil layer were 0-100 cm, in the crops of Forward hybrids, LG 56.32, LG 54.85, LG 55.82 were at planting densities of 60 thousand hectares, at the first sowing period - in the flowering phase - 127 mm. The optimal sunflower sowing period for LG 55.82 and LG 54.85 hybrids in the Right Bank steppe is soil warming up to a depth of seed 5-60C, for Forward and LG 56.32 hybrids is warming up to, a depth of seed 9-100C, optimal density - 60 thousand on ha. Under these conditions, the LG 55.82 hybrid produced a yield of 3.85 t / ha, the LG hybrid 54.85 - 3.64 t / ha, the Forward - 3.09 t / ha, the LG hybrid 56.32 - 3.62 t / ha. Taking into account the annual variation of weather conditions of spring sowing, it should be differentiated with regard to water and heat regimes.